Effect of DC Electric Field on the Emitted THz Signal of Antenna-Coupled Spintronic Emitters - Nandi, U.; Abdelaziz, M. S.; Jaiswal, S.; Jakob, G.; Gueckstock, O.; S Rouzegar, M. R.; Seifert, T. S.; Klaui, M.; Kampfrath, T.; Preu, S. (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2019)
We study the impact of an external electric DC field on antenna-coupled spintronic THz emitters driven by a 90 fs, 1550 nm laser oscillator. Simultaneous application of external electric and magnetic field shows a quadratic decrease in peak-peak THz pulse with increase in the bias voltage. We ascribe this decrease to Joule heating caused by the DC current flowing through the spintronic material.
CRIS-Team Scopus Importer:2023-03-27